PENGARUH MEDIA PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN BANTUAN HIDUP DASAR (BHD) (Studi Eksperimen Pada Perawat Pelaksana di Rumah Sakit TK. II Putri Hijau Medan Tahun 2017) - Resmi Pangaribuan; Mindo Tua Siagian; Asima Sirait (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2018)
ABSTRACT Emergency situation can occur wherever and whenever; it is the duty of health care providers to handle them. Death is usually caused bythe inability of health care providers to handle patients in the emergency situation (golden period)What is called by BHD (Basic Life Aid) is an attempt to keep the airway open, maintaining respiration, and circulation without any auxiliary apparatus. It is done by recognizing accurately the stop of heart beat and immediately gives circulation or ventilation aid. The objective of the research was to find out the influence of health education media on the knowledge of BHD; an experimental study on nurse practitioners at Putri Hijau Level II Hospital, Medan.The research used experimental analytic method with two group posttest design. The population was 110 nurse practitionerswho did not have certificates from BHD training. The data were gathered by using independent t-test. The result of the research showed that, statistically, audio visual and pantomime media had the influence on the increase in nurse practitioners’ knowledge of BHD. The result of independent t-test showed that pantomime was more effective than audio visual in increasing nurse practitioners’ knowledge of BHD. It is recommended that nurses increase their knowledge of BHD in immediately helping patients who need emergency aid and be ready in every emergency situation. The Head of the hospital should be wise in health education, increase nurse practitioners’ knowledge by providing counseling about BHD, using pantomime media. Keywords: Health Education Media, Knowledge, BLS (Basic Life Support)